Highly stable individual differences in the emission of separation calls during early development in the domestic cat. Issue 3 (April 2017) - Hudson, Robyn; Chacha, Jimena; Bánszegi, Oxána; Szenczi, Péter; Rödel, Heiko G.
Abstract: Study of the development of individuality is often hampered by rapidly changing behavioral repertoires and the need for minimally intrusive tests. We individually tested 33 kittens from eight litters of the domestic cat in an arena for 3 min once a week for the first 3 postnatal weeks, recording the number of separation calls and the duration of locomotor activity. Kittens showed consistent and stable individual differences on both measures across and within trials. Stable individual differences in the emission of separation calls across trials emerged already within the first 10 s of testing, and in locomotor activity within the first 30 s. Furthermore, individual kittens' emission of separation calls, but not their locomotor activity, was highly stable within trials. We conclude that separation calls provide an efficient, minimally intrusive and reliable measure of individual differences in behavior during development in the cat, and possibly in other species emitting such calls.